Prerequisites, general criteria and primary studies required in the CoalbedMethane prospecting and exploring: A review - Lemos de Sousa, M. J. (2006)
The main objectives of this paper are: (i) to review and summarize current concepts of Coalbed Methane (CBM) genesis and storage, (ii) to highlight and present the principal procedures and methodologies concerned with prospecting/exploring of CBM leading to a sequence of basic criteria to be followed at an early stage and, subsequently, during research and exploration, and (iii) to present a list of the most important analytical requirements during the investigations.